What Is Interesting and Relevant About Cybersecurity? NLP Analysis of a Survey of CS Students (Journal of The Colloquium for Information Systems Security Education, 2024)
Cyber attacks are a common feature of current news and many of them are the result of easy to avoid vulnerabilities in software. It is imperative that students graduating from an undergraduate Computer Science (CS) curriculum understand the consequences of vulnerable code. When developing lessons and assignments, it would be useful to have a sense of students’ attitude toward cybersecurity and appreciation of the need to write secure code. This paper describes an analysis of the results of a survey of students in core CS courses at our large public university, in which students answer free response questions about what they find interesting and relevant about cybersecurity. The survey was conducted in Fall 2022 and repeated in Spring 2023 after cybersecurity interventions were introduced into several core CS courses. We performed a Natural Language Processing (NLP) analysis of the free response answers to determine the overarching themes in the responses. We found that the most prevalent topics students are interested in are cryptography and penetration testing, and did not change over the two semesters. In answer to the question about the relevance of studying cybersecurity, we found that as students progress through the curriculum, what students find relevant moves from protecting their personal data to its importance in job duties and writing secure programs. When developing lessons and assignments, it may be helpful to introduce cryptography or penetration testing to engage students. Also, students should be taught early and often about the relevance of cybersecurity in their future job duties.
Keywords: cybersecurity education; natural language processing